A tutela dos interesses difusos como jurisdição diferenciada - Pamplona, Leandro Antonio (2016)
This study analyzes the diffuse rights consequences in the jurisdiction. It is necessary to rebuild logical thoughts with the identification and protection of collective rights several classic procedural institutes such as legitimacy, judgment and res judicata, developed based on individual conflicts. Nevertheless, this rethinking is accentuated further in the diffuse rights. Given the characteristics of these rights, especially for its indivisibility and the absolute indeterminacy of their holders by linking thus the whole community, remains settled a different court order. The need to think of a different jurisdiction to protect the diffuse rights is embodied in three main directions: 1) diffuse rights distinct nature (rights affecting all community); 2) the inevitability of the judge differentiated position of actions involving these rights; and 3) the law strength. Unlike the strict sense collective rights and individual homogeneous, diffuse rights belong to the whole community and reflect not just to individual level or a specific group. Given this situation the diffuse rights appear with collective relevance. From this point it is justified a more active role of the judge and greater social responsibility that allows the necessity to perform the control the part that send this right to justice, and also to supplement or amend the application or issue in the case. Indeed, the changes are not restricted to the process. The action that seeks to promote diffuse rights is the community participation in public policy. The judge promoting these rights, in the end defines public policies and their decision has not just a judicial nature. It has also strong administrative content, to support a different jurisdiction in actions involving diffuse rights, deeply committed to the common good.